2021
DOI: 10.7759/cureus.14870
|View full text |Cite
|
Sign up to set email alerts
|

Rectus Sheath Hematoma Due to Low Molecular Weight Heparin in a COVID-19 Patient in Turkey

Abstract: This case report presents a large left rectus sheath hematoma (RSH) case developed in a COVID-19 patient who had received no anticoagulant therapy before hospital admission. It discusses the patient’s diagnosis and treatment process. A 78-year-old woman was admitted to the ED with acute cough and shortness of breath. On CT scan, the pulmonary findings were consistent with COVID-19 pneumonia. Subcutaneous enoxaparin sodium was started to the patient, in accordance with the COVID-19 treatment guidelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Yeoh et al [ 17 ] recommend suspecting it in patients with significant groin, flank, abdominal, back pain, or hemodynamic instability after an interventional procedure or in anticoagulated patients. As shown by Kalayci [ 11 , 12 ], the ideal and straightforward diagnostic method is to check the hemoglobin level regularly. A contrast-enhanced CT scan of the abdomen remains the imaging modality of choice for early detection and prompt intervention [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yeoh et al [ 17 ] recommend suspecting it in patients with significant groin, flank, abdominal, back pain, or hemodynamic instability after an interventional procedure or in anticoagulated patients. As shown by Kalayci [ 11 , 12 ], the ideal and straightforward diagnostic method is to check the hemoglobin level regularly. A contrast-enhanced CT scan of the abdomen remains the imaging modality of choice for early detection and prompt intervention [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Tanal et al's [2] findings of non-traumatic focused hemorrhages are unexpected. Several clinical reports [7][8][9][10][11][12] describing cases of severe spontaneous abdominal or retroperitoneal bleeding were published during the most fulminant phase of the pandemic. Retroperitoneal hematoma is a rare radiologically diagnosed complication, defined as bleeding in the retroperitoneal space, usually without associated trauma or iatrogenic manipulation.…”
Section: Introductionmentioning
confidence: 99%
“…Kalayci et al recommended that enoxaparin must be discontinued immediately upon the detection of RSH. The patient's vital signs, abdomen condition, and hemoglobin levels should be evaluated regularly (3). Analgesia, management of predisposing factors, and discontinuation of anticoagulation are all effective treatments for most RSHs.…”
Section: Discussionmentioning
confidence: 99%
“…Global upsurge in COVID19 cases has been marked with systemic manifestations. Clinical studies have indicated thromboembolic events and vascular injuries in COVID19 patients [ 1 , 2 ]. In such cases, morbidities, poor prognosis and even mortality is reported.…”
Section: Introductionmentioning
confidence: 99%